Pengaruh Asset Growth, Intrinsic Value Dan Nilai Tukar Mata Uang Asing Terhadap Harga Saham Pada Perusahaan Sektor Keuangan Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2011-2015 - Muhammad Luthfi (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2018)
Asset growth is the growth of assets from year to year. The higher asset growth of thecompany indicates the company has the opportunity to do business development. Intrinsic value ofshares is the value used to assess whether a stock is in an undervalued or overvalued position. Theinteraction of international trade or multinational companies requires a means of payment that isacceptable to each country. Especially the exchange rate of the United States currency is the USdollar (USD) is accepted in many countries. The purpose of this research is to know the asset growth,intrinsic value and foreign exchange rate to share price at company of financial sector at IndonesiaStock Exchange. Data used is time series data 2011 - 2015 by using method of OLS (Ordinary LeastSquare). The results showed that intrinsic value partially has a significant influence on stock prices.While Asset growth and foreign exchange rates partially have no significant effect on stock prices.Asset growth, intrinsic value and foreign exchange rates simultaneously affect the stock prices offinancial sector companies listed on the Indonesia Stock Exchange in 2011-2015